Ethnobotany of Dayak medicinal plants in Kayu Ara village, Landak regency as a learning resource - Dede Sunarya; Hanum Mukti Rahayu; Ari Sunandar (University of Muhammadiyah Malang, 2024)
The lack of scientific documentation on the ethnobotany of Dayak medicinal plants makes this knowledge vulnerable to disappearing. Ethnobotany as a learning resource is one very effective step to make students more familiar with and love the knowledge of their ancestors. The purpose of this study was to determine the kinds of drugs and plants used by the community in Kayu Ara village and also the potential of ethnobotany of Dayak medicinal plants as a learning resource. This research uses a qualitative method where researchers divide 2 stages of research from collecting medicinal plant data by interview and observation. Interviews were conducted using snowball sampling technique. Further data collection is in the form of questionnaire results of potential biology learning resources. The results of the study found 21 types of medicinal plants which are divided into 16 families. The most widely used part is the leaves 45% and the least part of the fruit is only 3%. Potential learning resources obtained Clarity of Potential 88.89%, Suitability with Purpose 100%, Clarity of Target 91.67%, Clarity of Information Revealed 88.89%, Clarity of Exploration Guidelines 100%, Clarity of Expected Gain 100%. These results indicate that the ethnobotany of Dayak medicinal plants in kayu ara village, jelimpo sub-district, landak district is very effective in being used as a biology learning resource, especially in class X on biodiversity subject matter.